Discontinuation pattern of norplant among implant acceptors at the family planning clinic, University College Hospital, Ibadan, Nigeria (2006)
This is a retrospective study of 136 Norplant acceptors. We assessed the reasons for the discontinuation during the prescribed 5-year period of use. The continuation rates for the first, second and third years were 94.1%, 83.8%, and 79.4% respectively. The commonest reason for discontinuation was menstrual irregularities (40.43%) of clients followed by the desire for pregnancy in 29.79%. Contraceptive failure as a reason for discontinuation of Norplant use was not recorded in any of the clients in this series. In conclusion, ii is our belief that to sustain high continuation rates of Norplant use the clients require proper and effective counselling and support on the side effects of irregular bleeding patterns, which when occurs will be better coped with